(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
During last few years, continuous progresses in wireless communication have open new research fields in computer network. VANET proposes communication between vehicles by wireless means has a large potential to improve safety and travel comfort of passenger. Moreover automobile traffic safety is a major issue in developed area in which there may be misbehaving of traffic safety due to lack of controls or misguiding from the attacker end. Due to this, there is high amount of wastage of time and resources travelling through traffic congestion and misrouting of the vehicles by external source. For the sake of this, we propose an algorithm for VANET in which we show the effect of and further remove it by actual path routing and communication using distance algorithm to further improve the traffic pattern.Â